Spin-projected charge conductance in SNN junctions with noncentrosymmetric superconductors - T. H. Kokkeler; Y. Tanaka; A. A. Golubov (Physical Review Research, 2023)
A superconductor–normal-metal–normal-metal junction in which the superconducting potential is a mixture between s-wave and p-wave potentials is investigated using the Usadel equation equipped with Tanaka-Nazarov boundary conditions. This Research Letter provides several ways to distinguish between s-wave+chiral p-wave superconductors and s-wave+helical p-wave superconductors and a way to determine whether a superconductor has a mixed pair potential. Thus it is of great importance in the determination of the pair potential of superconductors. It is shown that the different spin sectors satisfy independent equations and can thus be calculated separately even if the d vector depends on the direction of momentum. This greatly simplifies the equations to be solved. It was found that a difference in conductance for sectors with opposite spins arises if both an s-wave component and a p-wave component are present, even in the absence of a magnetic field. It is shown that the spin-projected charge conductance for s-wave + chiral p-wave junctions and s-wave + helical p-wave junctions is qualitatively similar. A setup containing two superconductor–normal-metal junctions is shown to give a clear difference between the two types of superconductivity.